Defining the genetic contribution of type 2 diabetes mellitus. Issue 9 (1st September 2001) - van Tilburg, Jonathan; van Haeften, Timon W; Pearson, Peter; Wijmenga, Cisca
Abstract : Type 2 diabetes mellitus is a common multifactorial genetic syndrome, which is determined by several different genes and environmental factors. It now affects 150 million people world wide but its incidence is increasing rapidly because of secondary factors, such as obesity, hypertension, and lack of physical activity. Many studies have been carried out to determine the genetic factors involved in type 2 diabetes mellitus. In this review we look at the different strategies used and discuss the genome wide scans performed so far in more detail. New technologies, such as microarrays, and the discovery of SNPs will lead to a greater understanding of the pathogenesis of type 2 diabetes mellitus and to better diagnostics, treatment, and eventually prevention.